Attitudes, perceptions and views of Arab pharmacists and pharmacy students regarding the effectiveness of e-learning and web 2.0 tools in transferring of pharmaceutical knowledge - Alkoudmani, Ramez M. (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2017)
E-learning is considered one of the major trends in the digital age. Online learning helps pharmacy students and pharmacy practitioners to continue their professional development and to improve their skills via the internet. E-learning has positive effects on medical and pharmacy education in developed countries. Educators nowadays can build online educational materials based on their students learning styles and manage the learning process through learning management systems. However, scarce research efforts have been observed about the effectiveness of e-learning and web 2.0 tools in pharmacy education regarding transferring of pharmaceutical knowledge in Arabic Language Speaking Countries (ALSCs). This study consolidated into two phases. In the first phase a cross-sectional study design has been adopted to evaluate the attitudes and perceptions of Arab pharmacists and pharmacy students. While one-group pre-test post-test study design has been used in the second phase to assess the effectiveness of using e-learning and web 2.0 tools and explore the views of study participants regarding the effectiveness of using these technologies in transferring of pharmaceutical knowledge. The study results showed that the majority of respondents have highly positive attitudes towards using e-learning and emerging web 2.0 tools in transferring pharmaceutical knowledge. Similarly, the majority of them have high confidence level in learning and shared the same motivation to learn using such novel tools. Using Schoology® as LMS and Facebook® as the most popular social network site was effective. Upon completion of the online course, a significant improvement in the participants' level of knowledge about the studied topic has been observed. Highly positive views of respondents regarding the effectiveness of e-learning and web 2.0 tools have been perceived. Major logistical and technical barriers imped the successful adoption of e-learning in ALSCs. However, this study showed a promising results regarding using novel online educational technologies in transferring of pharmaceutical knowledge. Further researches are encouraged to study the convenient, compatibility and the effectiveness of e-learning and web 2.0 tools in pharmacy education in ALSCs. A steady expansion in the digital gap between ALSCs and developed nations empowers launching well-planned initiatives to facilitate the proper use and implementation of novel technologies in pharmacy education.